Caspase-3 and caspase-8 expression in breast cancer: caspase-3 is associated with survival - Xuan, Pu; Storr, Sarah J.; Zhang, Yimin; Rakha, Emad; Green, Andrew R.; Ellis, Ian O.; Martin, Stewart G. (Springer Verlag, 2016)
Impaired apoptosis is one of the hallmarks of cancer. Caspase-3 and -8 are key regulators of the apoptotic response and have been shown to interact with the calpain family, a group of cysteine proteases, during tumorigenesis. The current study sought to investigate the prognostic potential of caspase-3 and -8 in breast cancer, as well as the prognostic value of combinatorial caspase and calpain expression. A large cohort (n = 1902) of early stage invasive breast cancer patients was used to explore the expression of caspase-3 and -8. Protein expression was examined using standard immunohistochemistry on tissue microarrays. High caspase-3 expression, but not caspase-8, is significantly associated with adverse breast cancer-specific survival (P = 0.008 and P = 0.056, respectively). Multivariate analysis showed that caspase-3 remained an independent factor when confounding factors were included (hazard ratio (HR) 1.347, 95% confidence interval (CI) 1.086–1.670; P = 0.007). The analyses in individual subgroups demonstrated the significance of caspase-3 expression in clinical outcomes in receptor positive (ER, PR or HER2) subgroups (P = 0.001) and in non-basal like subgroup (P = 0.029). Calpain expression had been previously assessed. Significant association was also found between high caspase-3/high calpain-1 and breast cancer-specific survival in the total patient cohort (P = 0.005) and basal-like subgroup (P = 0.034), as indicated by Kaplan–Meier analysis. Caspase-3 expression is associated with adverse breast cancer-specific survival in breast cancer patients, and provides additional prognostic values in distinct phenotypes. Combinatorial caspase and calpain expression can predict worse prognosis, especially in basal-like phenotypes. The findings warrant further validation studies in independent multi-centre patient cohorts.